The Implementation of a Five-Foundation-Based Curriculum for Building Student Character - Solihin, Rahmat; Nawawi, Habib Natsir (Universitas Islam Lamongan, 2025)
This study aims to analyze the planning, implementation, and evaluation of a five-foundation-based curriculum in shaping students’ character at Madrasah Ibtidaiyah Plus Asy-Syukriyyah. Using a qualitative field study approach, data were collected through observations, interviews with teachers and school administrators, and documentation of learning activities and flagship programs. The analysis was conducted descriptively through data reduction, presentation, and conclusion drawing. The findings reveal that curriculum planning was collaboratively developed through teaching modules emphasizing the integration of character values. Implementation was manifested in daily spiritual routines such as dhuha prayer, dhikr Al-Ma'tsurat, and the recitation of Asmaul Husna, as well as flagship programs such as Islamic Personal Development Program, Islamic Exhibition Event, Night of Faith and Piety Development, Shaum Sunnah, Tahajud call, and Maghrib Mengaji. Program evaluation was conducted regularly through coordination between the teachers and Dewan Lembaga Pendidikan Islam (LPI) or Islamic Educational Institution Council to ensure alignment with objectives. The study's novelty lies in its focus on the five-foundation-based curriculum, a model rarely examined in prior research, that integrates academic, spiritual, and moral dimensions within a cohesive character education framework. The findings contribute to understanding how a value-based curriculum can effectively cultivate holistic student character in Islamic elementary education.